MODERN TECHNOLOGIES AND WEBSITES FOR TEACHING THE ENGLISH LANGUAGE ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
This article discusses effective methods for teaching other languages as well as the use of internet and contemporary technologies in English language instruction.